The Influence of Digitalization Readiness, Digital Mindset and Digital Culture on Digitalization Value in Multibusiness Companies - Barlian, Noer Aisyah; Ratnasari, Vita (Transpublika Publisher, 2025)
In an era of increasingly massive technological disruption, companies are required to adapt and transform to remain relevant and competitive. Digital transformation has become a necessity, even for companies operating in regions with low technology adoption due to low human development indices. Therefore, multi-business companies undergoing digital transformation face various challenges, both internally and externally. This research aims to determine whether digitalization readiness, digital mindset, and digital culture influence digitalization value. The analysis method is quantitative, using a questionnaire that is subsequently analyzed with Structural Equation Modeling- Partial Least Square (SEM-PLS). The data used in this research is the result of a questionnaire survey aimed at employees in multi-business companies that use technology in their operational processes. The findings showed that Digitalization Readiness influences Digital Mindset and Digital Culture but does not have a direct effect on Digitalization Value. Digitalization Readiness has an effect on Digitalization Value through Digital Mindset, but not through Digital Culture. Ultimately, the key to maximizing the benefits of digitalization for multibusiness firms lies not only in being prepared and having a supportive culture, but also in cultivating a digital mindset. This mindset serves as the crucial path for creating value and should be the main focus for organizations aiming to fully embrace digital transformation.